Emotional Intelligence and Work Performance among Vocational Teachers - Ismail, Khuzainey; Mohd Nopiah, Zulkifli; Rasul, Mohd Sattar (Journal of Technical Education and Training, 2020)
Emotional intelligence (EI) is a crucial component of an educator for the effectiveness of the teaching and learning process. Vocational teachers in the Technical Vocational and Education And Training (TVET) programme have to handle various students during the teaching and learning process. The experience has equipped the vocational teachers at the Malaysian Public Skills Training Institution (MPSTI) with EI competencies. This study was conducted on the vocational teachers in MPSTI under the Ministry of Human Resources (MOHR) and the Ministry of Youth and Sport (MOYS) who taught the TVET programme based on the National Occupational Skills Standard (NOSS) module. This study aims to identify the relationship of EI towards work performance. This study used the quantitative approach and collected the data using simple random sampling with a total of 1,186 vocational teachers from 31 MPSTI in Peninsular Malaysia. The measurement model and structural model were analysed using the Partial Least Squares (PLS) with SmartPLS 3.0 software to assess and validate the reflective model. The results reveal that the path coefficient value is (Î² = 0.753, t = 43.395, p = 0) which indicates that the EI factor has a significant relationship with work performance. The model prediction accuracy (RÂ²) is at a moderate level with 0.567. The finding of this study reveals the features of vocational teachers with EI factor namely self-awareness, self-regulation, motivation, empathy and social skills. This study can guide the management in the MOHR and MOYS to establish guidelines for the vocational teachers by incorporating elements of EI.